25-Hydroxyvitamin D and Parathyroid Hormone Levels Are Independently Associated with the Hemoglobin A1c Level of Korean Type 2 Diabetic Patients: The Dong-Gu Study. - Seong-Woo Choi; Sun-Seog Kweon; Young-Hoon Lee; So-Yeon Ryu; Jin-Su Choi; Jung-Ae Rhee; Hae-Sung Nam; Seul-Ki Jeong; Kyeong-Soo Park; Hee Nam Kim; Min-Ho Shin (PLoS ONE, 2016)
In type 2 diabetic patients, the relationships between 25-hydroxyvitamin D and parathyroid hormone levels, and glycemic control, remain unclear. We evaluated associations between 25-hydroxyvitamin D, parathyroid hormone, and hemoglobin A1c levels after adjusting for other covariates, including log transformed 25-hydroxyvitamin D levels and log transformed parathyroid hormone levels, in Korean patients with type 2 diabetes. In total, 1,175 patients with type 2 diabetes were selected from 8,857 individuals who completed the baseline survey of the Dong-gu study, conducted in Korea from 2007 to 2010. After adjusting for other covariates, we found that the mean hemoglobin A1c level was inversely associated with the 25-hydroxyvitamin D level (Q1: 7.47% [7.30-7.63], Q2: 7.25% [7.09-7.40], Q3: 7.17% [7.02-7.32], Q4: 7.19% [7.02-7.35]; p for trend = 0.021, p for between groups = 0.050) and the parathyroid hormone level (Q1: 7.35% [7.19-7.51], Q2: 7.34% [7.19-7.50], Q3: 7.28% [7.13-7.43], Q4: 7.09% [6.94-7.24]; p for trend = 0.022, p for between groups = 0.048). However, the mean fasting glucose level was not associated with either the 25-hydroxyvitamin D or parathyroid hormone level. In conclusion, inverse associations were evident between hemoglobin A1c, 25-hydroxyvitamin D and parathyroid hormone levels in Korean patients with type 2 diabetes. The associations remained significant after adjusting for other covariates, including the log transformed 25-hydroxyvitamin D levels and log transformed parathyroid hormone levels.